2018
DOI: 10.1177/2333721418778196
|View full text |Cite
|
Sign up to set email alerts
|

Grandparent–Grandchild Relationships in Chinese Immigrant Families in Los Angeles: Roles of Acculturation and the Middle Generation

Abstract: Being a grandparent is an important social role for Chinese older adults. Despite an increasing number of older Chinese immigrants in the United States and the uniquely differing culture of the United States relative to Chinese culture, few studies focused specifically on Chinese immigrant families in the United States. By conducting four focus groups (n = 32) in Los Angeles, CA, this study aimed to explore grandparent–grandchild relationships in Chinese immigrant families in the U.S. We found that the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The traditional Chinese family structure may be the main mechanism that explains why many aged Chinese-Canadians prioritize the needs of their family over themselves. Many aged Chinese-American immigrants tend to speak little English and are dependent on their family for support [33,34]. Many of them live in an extended household and are the caregivers to their grandchildren [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional Chinese family structure may be the main mechanism that explains why many aged Chinese-Canadians prioritize the needs of their family over themselves. Many aged Chinese-American immigrants tend to speak little English and are dependent on their family for support [33,34]. Many of them live in an extended household and are the caregivers to their grandchildren [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Many aged Chinese-American immigrants tend to speak little English and are dependent on their family for support [33,34]. Many of them live in an extended household and are the caregivers to their grandchildren [34,35]. Consequently, Chinese-American grandparents may assimilate to various facets of American culture in order to identify with their grandchildren [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Ge, Wu, and Dong (2018) found that acculturation had a nonsignificant relationship with oral health, whereas Li, Matthews, and Dong (2018) found that higher levels of health literacy and acculturation were associated with higher likelihood of cancer screening behaviors. In considering social relationships, Xu, Chi, and Wu (2018) found that higher perceived gaps in acculturation between themselves and their grandchildren negatively impacted their relationship. Furthermore, articles in this issue detail how Traditional Chinese Medicine is relevant and still widely used among Chinese older adults in the United States ( Dong & Li, 2018 ), but this population simultaneously utilizes non-Western and Western forms of health care, especially with respect to preventive care ( Dong & Jiang, 2018 ).…”
Section: Study Findingsmentioning
confidence: 99%
“…They act as instructors, models, and interpreters, and provide financial, social, and/or emotional support to their parents and grandparents. Therefore, both children and grandchildren are an important group to consider when studying health behaviour of first-generation immigrants [34,35], since they frequently act as brokers for their parents or grandparents in contact with the Dutch healthcare [36].…”
Section: Methodsmentioning
confidence: 99%